PERBANDINGAN RISIKO DAN PENGEMBALIAN ANTARA SAHAM-SAHAM BERBASIS SYARIAH DAN NON SYARIAH YANG TERCATAT DI BURSA EFEK INDONESIA - Adhytya Bagus Rizkianto (Universitas muhammadiyah malang, 2016)
This research aims to determine the significant differentiation on risk and returns between sharia and non-sharia stocks based on Indonesian Stock Exchange. The Independent Sample T-Test was employed as an analytical tool. To measure the significant level of differentiation is using critical value < 0,05. The result shows that there was no significant differentiation of the risk and returns between sharia and non-sharia stocks based. The analysis also shows that the risk and returns of non-sharia higher than sharia stock based. Based on the results of data analysis, it could be recommended that investors be better to invest in sharia stock based because it has a lower risk than non-sharia stock based.